2016
DOI: 10.1002/masy.201400234
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bismuth Telluride Thin Film for Thermoelectric Application Via Electrodeposition Technique

Abstract: Summary Nanocrystalline Bismuth Telluride (Bi2Te3) thin film was electrodeposited potentiostatically at room temperature from acidic bath. In order to study their structural, morphological properties and compositional analysis of as synthesized thin film were systematically examined by X‐ray diffraction (XRD), scanning electron microscopy (SEM) and and energy dispersive spectroscopy (EDS). The crystallographic characterization of Bi2Te3 thin film was carried out using XRD and main diffraction peak at (015) pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The Seebeck coefficient of 32.89 μV/K was obtained (Yang et al, 2016). Patil et al (2016) electrodeposited thin Bi 2 Te 3 film in a solution with 10 mM Te(IV), 7 mM Bi(NO 3 ) 3 •5H 2 O and 1 M HNO 3 . The XRD pattern showed that the Bi 2 Te 3 film was nanocrystalline with grain size of 18.08 nm and had a preferred orientation of (015) with rhombohedral crystal structure (Patil et al, 2016).…”
Section: Electrodeposition Of Bismuth Telluride (Bi 2 Te 3 ) Based Materials Including Bite Bisbte Bitese and Bisbtesementioning
confidence: 99%
See 1 more Smart Citation
“…The Seebeck coefficient of 32.89 μV/K was obtained (Yang et al, 2016). Patil et al (2016) electrodeposited thin Bi 2 Te 3 film in a solution with 10 mM Te(IV), 7 mM Bi(NO 3 ) 3 •5H 2 O and 1 M HNO 3 . The XRD pattern showed that the Bi 2 Te 3 film was nanocrystalline with grain size of 18.08 nm and had a preferred orientation of (015) with rhombohedral crystal structure (Patil et al, 2016).…”
Section: Electrodeposition Of Bismuth Telluride (Bi 2 Te 3 ) Based Materials Including Bite Bisbte Bitese and Bisbtesementioning
confidence: 99%
“…Patil et al (2016) electrodeposited thin Bi 2 Te 3 film in a solution with 10 mM Te(IV), 7 mM Bi(NO 3 ) 3 •5H 2 O and 1 M HNO 3 . The XRD pattern showed that the Bi 2 Te 3 film was nanocrystalline with grain size of 18.08 nm and had a preferred orientation of (015) with rhombohedral crystal structure (Patil et al, 2016). Na et al (2016) electrodeposited n-type Bi 2 Te 3 films in the electrolyte with 10 mM HTeO 2 + , 8 mM Bi 3+ and 1 M HNO 3 on a flexible substrate.…”
Section: Electrodeposition Of Bismuth Telluride (Bi 2 Te 3 ) Based Materials Including Bite Bisbte Bitese and Bisbtesementioning
confidence: 99%
“…A few literatures are available on Bi 2 Te 3 as PEC and for STEG application. Patil et al [21] observed the fernshaped dendrites microstructure and rhombohedral crystal structure with crystallite size 18.08 nm of potentiostastically electrodeposited Bi 2 Te 3 thin films for thermoelectric application. Chaudhari et al [22] reported that, due to irradiation of proton beam with energy 7.5 MeV, single crystals of p-type Bi 2 Te 3 converted to n-type, and Hall coefficient increased while Hall mobility and magnetoresistance coefficient decreased with increasing radiation dose.…”
Section: Introductionmentioning
confidence: 99%